Assessing creative potential as student outcome: On the applicability of the TCT-DP in repeated measures - Theurer, Caroline; Berner, Nicole E.; Lipowsky, Frank (Thinking Skills and Creativity, 2016)
Within a constantly changing society, the ability to act creatively in various domains is becoming increasingly important. Schools are expected to react to this by educating their students in complex problem-solving skills and creative thinking (OECD, 2014). Teachers are therefore asked to foster creativity, which implies a need to learn more about assessing creativity or creative potential. When evaluating programs that are designed to foster creativity in and out of school, it is necessary to assess creativity as a criterion, even though this is a challenging thing to do. The difficulties become particularly apparent when it comes to investigating creativity development. The present study uses the Test for Creative Thinking-Drawing Production (Urban & Jellen, 1996) to take a closer look at the measurability of creativity during childhood. German students were tested three times while at elementary school (at the beginning of the first grade and at the end of the second and fourth grade). We tested measurement equivalence and found partially strong measurement invariance in a subset of the rating categories suggested in the test's manual. The proposed model is discussed theoretically and empirically, while keeping in mind that it is essentially a preliminary finding until replication studies have been conducted. The study indicates how creativity could be taken into account as a relevant student outcome in large-scale assessments.
CRIS-Team Scopus Importer:2023-04-11
Keywords: Creativity development; Elementary school; Invariance; Measurement; TCT-DP

Aufgabenkultur im Kunstunterricht der Grundschule - Berner, Nicole; Lotz, Miriam (Begabungen entwickeln & Kreativität fördern, 2015)

Auswertung der PERLE-Videostudien und Überblick über die Beobachtungsinstrumente - Hess, Miriam; Berner, Nicole; Gabriel, Katrin (Technischer Bericht zu den PERLE-Videostudien, 2013)

Bewusstes Üben ermöglichen - Berner, Nicole (Kunst und Unterricht, 2016)
Keywords: Unterrichtsqualität

Bildnerische Kreativität im Grundschulalter - Berner, Nicole (Kopaed, 2013)

"Das trau ich meiner Klasse zu!" Gestaltungsaufgaben im Fach Kunst und ihr Zusammenhang zur Einschätzung des Klassenleistungsniveaus durch die Lehrperson - Berner, Nicole; Theurer, Caroline; Hess, Miriam (Aufgaben als Schlüssel zur Kompetenz. Didaktische Herausforderungen, wissenschaftliche Zugänge und empirische Befunde, 2016)

Der Forschungsprozess in der empirischen kunstdidaktischen Forschung - Berner, Nicole (Forschen im Kunstunterricht, 2025)

Die Entwicklung der Kreativität und ihre Determinanten in den ersten beiden Grundschuljahren - Berner, Nicole; Lotz, Miriam; Kastens, Claudia; Faust, Gabriele; Lipowsky, Frank (Zeitschrift für Grundschulforschung, 2010)

Die Kodierung der inhaltsbezogenen Aktivitäten im Fach Kunst - Berner, Nicole; Schmidt, Rebekka; Lotz, Miriam; Stackmann, Sabine (Technischer Bericht zu den PERLE-Videostudien, 2013)

Die Kodierung von Rezeptionsphasen im Kunstunterricht - Schmidt, Rebekka; Lotz, Miriam; Berner, Nicole (Technischer Bericht zu den PERLE-Videostudien, 2013)

Gestaltungsaufgaben verständlich stellen - Berner, Nicole; Hess, Miriam (Kunst und Unterricht, 2016)

Grenzen öffnen – Werte prüfen: Bildungswerte und Wertebildung in der Kunstdidaktik. Transdisziplinäre Entwürfe und Ergebnisse einer bilateralen Online-Ringvorlesung - Berner, Nicole; Loffredo, Anna Maria (Kopaed, 2021)

Interdependencies Between Openness and Creativity of Fifth Graders - Theurer, Caroline; Rogh, Wida; Berner, Nicole (Psychology of Aesthetics, Creativity, and the Arts, 2021)
Openness to experience has become of special interest in the field of creativity research. Theoretical frameworks consider openness as one important individual feature that contributes to creative outcomes. Empirical results support this assumption, showing openness to be positively related to various creativity measures. However, studies on the relationship between creative outcomes and openness mainly focus on adults and differ in their operationalization of creativity. The present study analyzes the relationship between openness and different creativity measures in late childhood using a holistic measure to assess creative potential as well as divergent thinking tasks scored for ideational fluency and flexibility. Accounting for interdependencies over the 5th school year, the results show that (a) comparable with previous findings, there are low cross-sectional correlations between openness and creativity, and (b) openness and creativity develop independently in the period considered. Only divergent thinking slightly affects openness 1 year later (β =.084, p <.01). The study extends existing research by including childhood development. The results suggest that the relationship between creativity and openness consolidates with age. Implications for creativity research and the educational context are discussed while considering the limitations of the study.
CRIS-Team Scopus Importer:2023-04-11
Keywords: Childhood development; Creativity; Cross-lagged panel; Divergent thinking; Openness to experience

Kernfragen der Kunstdidaktik - Berner, Nicole (Haupt Verlag, 2022)

Kreative Methoden in Kunst und Design - Berner, Nicole; Rieder, Christine (2024)

Kreativität: Merkmale erkennen und fördern - Berner, Nicole (Kunst - Didaktik für die Grundschule. 1.-4. Schuljahr, 2013)

Kreativität über das Plastizieren fördern. Implikationen empirischer Befunde zur bildnerischen Kreativität im plastischen Gestalten - Berner, Nicole (Konsequenzen empirischer Forschung für den Kunstunterricht, 2013)

Niedrig und mittel inferente Kodierung: Aufgabenstellungen zum plastischen Gestalten - Berner, Nicole; Hess, Miriam (Technischer Bericht zu den PERLE-Videostudien – Band 2: Beobachtungssysteme zur Beschreibung und Qualität von Grundschulunterricht, 2019)

Roter Faden: Strukturieren und fokussieren - Berner, Nicole (Fachdidaktik Kunst, 2013)

Schaffen Frei-Räume Kreativität? Zur Offenheit von Aufgabenstellungen im Fach Kunst - Berner, Nicole; Hess, Miriam; Lipowsky, Frank (Räume für Bildung – Räume der Bildung. Beiträge zum 25. Kongress der Deutschen Gesellschaft für Erziehungswissenschaft, 2018)

Schülerdaten – Abschlusserhebung (Ende 2. SJ.) - Mösko, Emely; Schoreit, Edgar; Poloczek, Sebastian; Lotz, Miriam; Berner, Nicole; Theurer, Caroline; Lipowsky, Frank (Instrumente: Schüler, Eltern (Messzeitpunkte 2 & 3), 2011)

Tiefenräumliche Darstellungskonzepte im fünften Schuljahr – Ergebnisse und kunstdidaktische Folgerungen - Berner, Nicole (BÖKWE, 2015)

Typisch Mädchen – typisch Junge? Empirische Befunde zu geschlechtsspezifischen Unterschieden im plastischen Gestalten von Grundschulkindern - Berner, Nicole (U20 - Kindheit Jugend Bildsprache, 2013)

Unterrichtsbeobachtung im Projekt PERLE - Lotz, Miriam; Berner, Nicole; Gabriel, Katrin; Post, Swantje; Faust, Gabriele; Lipowsky, Frank (Grundlegende Bildung ohne Brüche, 2011)

Zum Zusammenhang von Schulnoten und Kreativität im Kunstunterricht der Grundschule – Erste Befunde - Berner, Nicole; Lotz, Miriam; Theurer, Caroline (Individuelle Förderung und Lernen in der Gemeinschaft, 2014)